Active tectonic deformation along rejuvenated faults in tropical Borneo: Inferences obtained from tectono-geomorphic evaluation - Manoj Joseph Mathew, David Menier, Numair Siddiqui, Shashi Gaura, . (2016)
The island of Borneo is enveloped by tropical rainforests and hostile terrain characterized by high denudation rates. Owing to such conditions, studies pertaining to neotectonics and consequent geomorphic expressions with regard to surface processes and landscape evolution are inadequately constrained.